(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Bamboo shoots, the tender young sprouts of bamboo plants are a staple in the diets of many people in Northeast India. It is celebrated for their unique texture and subtle flavor and impressive nutritional profile. This article explores their nutritional value through a literature review and highlights their cultural significance and potential for inclusion in modern diets. A survey of 30 respondents (15 males and 15 females aged 18-65) from Northeast India provided insights into the cultural and culinary and modern dietary aspects of bamboo shoots. Findings reveal that bamboo shoots are integral to traditional ceremonies and festivals which symbolize prosperity with new beginnings along resilience and strength and protection. They are regularly consumed in various traditional dishes such as fish and meat curries including stir fries and pickles and soups and stews and fermented dishes like khorisa. Common preparation methods include boiling and fermentation and pickling also with stir frying and stewing. The literature review highlights bamboo shoots low caloric and fat content having high dietary fiber and rich vitamin and mineral composition including vitamin B6 vitamin E potassium and manganese. These attributes contribute to their health benefits such as aiding weight management helping in digestive health and regulating blood sugar and reducing the risk of chronic diseases. The survey also indicates a strong potential for incorporating bamboo shoots into modern diets with a majority of respondents aware of their nutritional benefits and open to including them in daily meals. Factors such as the availability of ready to cook products and increased awareness of health benefits and convenience in preparation are crucial for encouraging greater consumption. This research underscores the importance of bamboo shoots in promoting health, culinary diversity, and cultural heritage in Northeast India.